Faktor - Faktor yang Berhubungan dengan STBM di Desa Lhok Makmur Kecamatan Simeulue Barat, Kabupaten Simeulue Tahun 2023 - Julisma Julisma; Darmawan Darmawan; Ihsan Murdani; Kiswanto Kiswanto; Sufyan Anwar (Jurnal Syntax Admiration, 2024)
Lhok Makmur Village located in West Simeulue Sub-District, Simeulue Regency, most of the community has not accessed STBM eitherpillars 1-5 STBM, which was caused by a lack of community willingness to access the STBM program. The purpose of this study was to determine the factors that influence STBM in Lhok Makmur Villager. The method used in this study was quantitative with an observational design through a cross sectional approach, the population in this study were 236 families, the sample in this study were 80 heads of families (KK) or housewives (IRT) the sampling technique was carried out by random  sampling. Data were collected using a questionnaire and then analyzed using Univariate  and Bivariate Analysis with the help of the SPSS version 26 application. The results of the  study based on the results of Bivariate Analysis on the variables of education (p value =  0.073), occupation (p value = 0.584), income (p value = 1.000), there was no statistically  significant effect with the dependent variable, while on the awareness variable (p value =  0.019), and the participation variable (p value = 0.001) there was a significant effect with the  dependent variable, in the community in Lhok Makmur Village, West Simeulue District, Simeulue Regency. The conclusion of the five independent variables studied was that there are two variables that have an impact, namely, (community awareness and community participation) while the variables (education, employment, income) do not have a statistically significant effect on the dependent variable (STBM). Suggestions for the Puskesmas Sanggiran to be able to collaborate with the Village Apparatus to involve active participation or community empowerment to increase more understanding of the importance of access to STBM programs.